2012
DOI: 10.1007/s00540-012-1469-4
|View full text |Cite
|
Sign up to set email alerts
|

Microglial activation involved in morphine tolerance is not mediated by toll-like receptor 4

Abstract: Microglial activation caused by a mechanism independent of TLR4 is involved in the development of morphine tolerance. Further studies are necessary to clarify the cellular mechanisms of morphine-induced microglial activation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
50
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(54 citation statements)
references
References 14 publications
3
50
1
Order By: Relevance
“…However, a recent study by Fukagawa and colleagues [39] reported a dissociation between TLR4 and opioid tolerance; they found that morphine tolerance develops in the absence of TLR4. Here, we examined the link between TLR4 and opioid analgesia in two inbred mouse strains: C3H/HeJ mice which have a dominant-negative point mutation in the Tlr4 gene, and B10ScNJ mice which are null mutants for TLR4.…”
Section: Discussionmentioning
confidence: 96%
“…However, a recent study by Fukagawa and colleagues [39] reported a dissociation between TLR4 and opioid tolerance; they found that morphine tolerance develops in the absence of TLR4. Here, we examined the link between TLR4 and opioid analgesia in two inbred mouse strains: C3H/HeJ mice which have a dominant-negative point mutation in the Tlr4 gene, and B10ScNJ mice which are null mutants for TLR4.…”
Section: Discussionmentioning
confidence: 96%
“…There are many hypotheses about how opioid tolerance develops, including, functional decoupling of opioid receptors from G-proteins which leads to receptor desensitization, phosphorylation of opioid receptors, internalization and/or down-regulation of μ-opioid receptor, upregulation of the cAMP (cyclic adenosine monophosphate) and PKC (protein kinase C) pathways, neuroimmune activation and neuroinflammation, glutamate homeostasis, nitric oxide production, modulatory role of ion channels or neurotrophic factors and activation of glial cells (astrocytes and microglia) at the level of the spinal cord (Ben-Eliyahu et al, 1992;Bian et al, 2012;Dang and Christie, 2012;DeLeo et al, 2004;Fukagawa et al, 2013;Koch and Höllt, 2008;Kolesnikov et al, 1993;Martini and Whistler, 2007;Ossipov et al, 2004;Vacca et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…However, there are several other findings that may temper the promise of reported interactions among TLR4 antagonists and abused drugs. In particular, recent studies have not confirmed involvement of TLR4 in morphine-induced tolerance or dependence (Fukagawa et al, 2013;Skolnick et al, 2014;Stevens et al, 2013) or the attenuation of tolerance produced by the microglial inhibition (Fukagawa et al, 2013). Further, a recent paper (Mattioli et al, 2014) demonstrated with in vivo studies that morphine-induced tolerance, hyperalgesia and physiological dependence was retained in TLR4 genetically modified null mice.…”
Section: Introductionmentioning
confidence: 95%